Clinical Pharmacy Interventions In The ICU At A Tertiary Hospital In Jordan - Massad, Eman MOh'd; Ashran, Walaa Jihad; Daoud, Sana Mueen; Abu Ajamieh, Mays Waleed; Bohy, Doaa El- (Journal of Neonatal Surgery, 2025)
Background: Clinical pharmacists play a crucial role in Intensive Care Units by optimizing medication therapy, preventing adverse drug events, and contributing to improved patient outcomes. Despite their significance, limited data exist on the specific impact of clinical pharmacy interventions in ICUs within Jordan. Objective: This study aims to identify the types and frequency of clinical pharmacist interventions across four main ICUs namely neonatal, pediatric, medical, and surgical ICUs at a tertiary academic hospital in Jordan. Additionally, it seeks to determine the most frequent treatments associated with these interventions. Methods: A retrospective descriptive study was conducted at Jordan University Hospital from January 2024 to June 2024. Clinical pharmacist intervention records were reviewed, and data were collected on patient demographics, types of medications, and categories of interventions. The interventions were classified according to a standardized system based on clinical pharmacy guidelines. Results: Dosage regimen adjustments were the most common intervention across all ICUs, particularly in the NICU (86.7%) and PICU (58%). The MICU had a high rate of interventions related to unnecessary drug therapy (25.6%) and additional diagnostic tests (42.8%). In the SICU, enoxaparin (12.5%) was among the most frequently adjusted medications. Antibiotic stewardship was a key area of pharmacist intervention, with vancomycin being the most frequently adjusted antibiotic across all ICUs. Conclusion: Clinical pharmacists contribute significantly to patient care in ICUs by ensuring appropriate medication use, preventing errors, and optimizing therapy. The findings support the need for continued integration of clinical pharmacists in ICU teams to enhance patient safety and improve clinical outcomes. Future research should focus on evaluating the long-term impact of these interventions on patient morbidity, mortality, and cost-effectiveness.